The foxhole court eaudiobook - Sakavic, Nora (All For the Game, 2018)
Neil Josten is the newest addition to the Palmetto State University Exy team. He's short, he's fast, he's got a ton of potential—and he's the runaway son of the murderous crime lord known as The Butcher. Signing a contract with the PSU Foxes is the last thing a guy like Neil should do. The team is high profile and he doesn't need sports crews broadcasting pictures of his face around the nation. His lies will hold up only so long under this kind of scrutiny and the truth will get him killed. But Neil's not the only one with secrets on the team. One of Neil's new teammates is a friend from his old life, and Neil can't walk away from him a second time. Neil has survived the last eight years by running. Maybe he's finally found someone and something worth fighting for.